Downregulation of myc promoter-binding protein 1 (MBP-1) in growth-arrested malignant B cells - Tvrdík, Daniel; Dundr, Pavel; Povýšil, Ctibor; Přikryl, Petr; Melčáková, Štěpánka; Planková, Martina (Folia biologica (Praha), 2007)
Normal human B lymphocytes are sensitive to the growth-inhibitory action of TGF-beta1 whereas malignant B lymphoma cells are mostly resistant to TGF-beta1 effects. We have shown in our previous work that, TGF-beta1 treatment resulted in significant growth inhibition of the DoHH2 cell line. In the present study we showed that TGF-beta1-induced growth arrest was associated with notable downregulation of the myc-binding protein-1 (MBP-1). Moreover, our results indicated that c-Myc overexpression in TGF-beta1-arrested malignant B cells is mediated by binding of MBP-1, as a transcription repressor, to the (+118/+153) element of the promoter region of the myc gene.
Keywords: polymerázová řetězová reakce; Proto-Oncogene Proteins c-myc; TATA Box; Promoter Regions, Genetic; Transforming Growth Factor beta1; protoonkogenní proteiny c-myc; Electrophoresis, Gel, Two-Dimensional; Financing, Organized; Blotting, Western; western blotting; 2D gelová elektroforéza; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Lymphoma, Follicular; transformující růstový faktor beta1; Polymerase Chain Reaction; TATA box; financování organizované; folikulární lymfom; promotorové oblasti (genetika)